Peristilahan Satuan Ukuran Dalam Bahasa Melayu Kapuas Hulu - Lasmini, Anti Moni; Madeten, Sisilya Saman; Muzammil, Ahmad Rabi’ul (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Lasmini, Anti Moni. 2022. The unit of measure has an important role in the life of the BMKH speaker community and has even become a habit that is passed down from generation to generation. The unit of measure is the effort used to express the measurement results, standard or basis of measurement. In Indonesian, the units of measurement that we use are kilo, gram, kg, ounce, meter, ton, and cm. similarly, BMKH also has traditional units of measurement that state units of length, quantity, unit of content, weight and magnitude. This traditional unit of measure also functions to measure the quantity of an object and contains the value and meaning of culture and culture in the community that owns the culture. This study aims to describe and document the terminology of the unit of measure in the BMKH Researchers choose a unit of measure as the object of research to preserve culture through language. This research was conducted in Temuyuk Village, Bunut Hulu District, Kapuas Hulu Regency. The method used in this study is a descriptive method with a qualitative research form. The approach used in this research is semantics. The technique used in this research is direct observation, interview technique, fishing technique, surface speaking technique, recording technique and note-taking technique. The data collection tool in this study was a writing instrument voice recorder for taking notes, and the researcher as the main instrument. Based on the results of the analysis, there are five clarifications in the terminology of the BMKH unit of measure, namely based on the category of terminology in terms of units of measure, meaning and meaning in units of measure.